The Study of User Satisfaction with the Website Services of the Faculty of Economics and Business Administration, Thaksin University - Sriwan, Anukoon (Journal of Management Sciences, Songkhla Rajabhat University, 2025)
This study aimed to: 1) investigate the level of user satisfaction with the website of the Faculty of Economics and Business Administration, Thaksin University; and 2) examine the influence of website quality factors on user satisfaction. The sample consisted of 400 individuals, including faculty personnel, students, academic service users, and high school students (Grade 12) as well as vocational certificate students (equivalent to higher vocational education), who had accessed the Faculty’s website. Purposive sampling was employed for data collection. A questionnaire was used as the research instrument. Data were analyzed using descriptive statistics percentage, mean, and standard deviation as well as inferential statistics, specifically multiple regression analysis, with the significance level set at 0.05. The results revealed that the overall satisfaction level of website users was high ( =4.08). Hypothesis testing showed that website quality factors namely system quality (β=0.500), perceived usefulness (β=0.235), and perceived ease of use (β=0.175) had a statistically significant influence on user satisfaction at the 0.05 level. These factors collectively explained 54.9% of the variance in user satisfaction (Adjusted R² = 0.549). In conclusion, website design that allows users to use it easily, access the information they need quickly, and use a quality system has a significant impact on user satisfaction.